Cryospectrokinetic characterization of intermediates in biochemical reactions: carboxypeptidase A. - Auld, D S (1984)
Cryospectrokinetic studies provide concurrent structural, kinetic, and chemical data on short-lived intermediates in the course of the interactions of enzymes with their substrates and of other, similar pairs of biomolecules. Subzero temperatures extend the lifetimes of these intermediates and, combined with rapid-mixing and rapid-scanning instrumentation, allow simultaneous measurement of both their physical-chemical and kinetic characteristics. For carboxypeptidase A, the spectra of a chromophoric, enzymatically functional cobalt atom at the active site signal the structure of the coordination complex during catalysis, while radiationless energy transfer between enzyme tryptophans and the fluorescent dansyl blocking group of rapidly hydrolyzed peptide and ester substrates provides the basis for measurement of the rates of formation and breakdown of intermediates. Subzero radiationless energy transfer kinetic studies of the zinc and cobalt enzymes disclose two intermediates in the hydrolysis of both peptides and esters and furnish all the rate and equilibrium constants for the reaction scheme E + S in equilibrium ES1 in equilibrium ES2----E + P. The chemical and kinetic data indicate that neither of these is an acylenzyme intermediate. Both absorption and EPR spectra of the ES2 reaction intermediates consistently demonstrate the formation of transient metal complexes, differences between the effects induced by peptides and esters, and strong similarities between those induced by all peptides on the one hand and all esters on the other. The marked alterations of the cobalt spectra likely reflect the coordination of a substrate carboxyl and/or carbonyl group to the metal at a critical step in the course of catalysis. The cryospectrokinetic approach developed here in the mechanistic study of this metalloenzyme is applicable to the examination of transients of biochemical reactions in general. It will allow molecular characterization of previously elusive intermediates and greatly magnify the range of mechanistic questions that can be answered.